2022
DOI: 10.3390/molecules27123806
|View full text |Cite
|
Sign up to set email alerts
|

The Extracts of Polygonum cuspidatum Root and Rhizome Block the Entry of SARS-CoV-2 Wild-Type and Omicron Pseudotyped Viruses via Inhibition of the S-Protein and 3CL Protease

Abstract: COVID-19, resulting from infection by the SARS-CoV-2 virus, caused a contagious pandemic. Even with the current vaccines, there is still an urgent need to develop effective pharmacological treatments against this deadly disease. Here, we show that the water and ethanol extracts of the root and rhizome of Polygonum cuspidatum (Polygoni Cuspidati Rhizoma et Radix), a common Chinese herbal medicine, blocked the entry of wild-type and the omicron variant of the SARS-CoV-2 pseudotyped virus into fibroblasts or zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Modifications of VNT have been described in the scientific literature to investigate the antiviral properties of such herbal extracts [ 51 ]. However, only laboratory testing models with a wild-type virus can most suitably mimic the natural viral infection of the host by allowing long-term virus–cell contact with prolonged antiviral contact of the virus extract in the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modifications of VNT have been described in the scientific literature to investigate the antiviral properties of such herbal extracts [ 51 ]. However, only laboratory testing models with a wild-type virus can most suitably mimic the natural viral infection of the host by allowing long-term virus–cell contact with prolonged antiviral contact of the virus extract in the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Water and 90% ethanol (aq) extracts of Japanese knotweed rhizome and root blocked the entry of SARS-CoV-2 pseudotyped virus into HEK293T-ACE2 cells and zebrafish larvae and were shown to inhibit the spike protein–ACE2 receptor interaction and 3CL protease activity. Anti-SARS-CoV-2 activity was confirmed for the extract component gallic acid [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers further found that among the 9 major phytochemical constituents in these PC extracts, only gallic acid significantly inhibited viral entry into HEK293T cells in a dose-dependent manner, with an IC 50 value of 23.5 μmol/L (Lin et al. 2022 ). Other studies have shown that EtOAc extract from the root of PC (12.5 μg/mL) could suppress the expression of Epstein-Barr virus lytic proteins and transcriptional genes, and the transcriptional inhibition rates of lytic genes BRLF1 and BZLF1 are 95.29% and 95.31%, respectively (Yiu et al.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…A withanone-enriched extract from Withania somnifera leaves has been found to be effective in mitigating the pathological responses induced by the SARS-CoV-2 recombinant spike (S) protein in humanised zebrafish. This extract was found to prevent skin haemorrhaging, modulate the immune response in the swim bladder and attenuate kidney necrosis(Balkrishna, Verma, et al, 2021;.Other studies have explored the effects of Polygoni Cuspidati Rhizoma et Radix and Polygoni Multiflori Radix extracts on pseudovirus entry in zebrafish larvae Lin et al (2022). found that water and ethanol extracts of Polygoni Cuspidati Rhizoma et Radix were effective in reducing the entry of both wild-type and omicron pseudotyped viruses in an intact zebrafish model.…”
mentioning
confidence: 99%